Teaching lecture notetaking with authentic materials. (17th October 2018) - Siegel, Joseph
Abstract: Authentic materials such as TED Talks have become an everyday presence in the ELT classroom, often for practice listening and taking notes. However, teachers can struggle to teach the sub-skills that are involved in notetaking, and instead often simply tell students to 'take notes'. This approach lacks the scaffolding required for the complex activity. When unpredictable and loosely structured authentic materials are used for notetaking, students can be overwhelmed and teachers left with few pedagogic ideas. To address the need for pedagogy for teaching notetaking with authentic materials, this paper reports a project that introduced a four-step pedagogic sequence in conjunction with TED Talks to upper secondary school students in Sweden. Analysis of pre- and post-intervention comprehension tests and samples of notes suggests that the sequence has positive effects, particularly regarding the quantity of notes recorded. The paper describes and provides justification for each step of the approach and discusses the pedagogic implications.